1998
DOI: 10.1152/jappl.1998.84.1.257
|View full text |Cite
|
Sign up to set email alerts
|

Does adipose tissue influence bioelectric impedance in obese men and women?

Abstract: Bioelectric-impedance analysis overestimates fat-free mass in obese people. No clear hypotheses have been presented or tested that explain this effect. This study tested the hypothesis that adipose tissue affects measurements of resistance by using data for whole body and body segment resistance and by using muscle, adipose tissue, and bone volumes from magnetic resonance imaging for 86 overweight and obese men and women (body mass index > 27 kg/m2; age 38.5 +/- 10.2 yr). In multiple-regression analysis, muscl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
83
0

Year Published

1998
1998
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 96 publications
(86 citation statements)
references
References 15 publications
3
83
0
Order By: Relevance
“…For one, aging must cause a number of anatomic and physiologic changes that in¯uence electrical conduction independent from¯uid distribution effects. Moreover, relative adiposity tends to increase with age and this could play a role, although small one, in determining total tissue conductivity (Baumgartner et al, 1998). Our ®ndings suggest that additional basic BIA studies are needed to improve understanding of appendicular conduction pathways, although at an empirical level development of good skeletal muscle mass prediction models is possible.…”
Section: Discussionmentioning
confidence: 90%
“…For one, aging must cause a number of anatomic and physiologic changes that in¯uence electrical conduction independent from¯uid distribution effects. Moreover, relative adiposity tends to increase with age and this could play a role, although small one, in determining total tissue conductivity (Baumgartner et al, 1998). Our ®ndings suggest that additional basic BIA studies are needed to improve understanding of appendicular conduction pathways, although at an empirical level development of good skeletal muscle mass prediction models is possible.…”
Section: Discussionmentioning
confidence: 90%
“…In obese women, however, using the bio-electrical impedance method, FFM could be slightly overestimated by about 3 kg. 24 Correlation analysis (Table 3) All absolute isokinetic strength measurements correlated only weak to moderately positive with absolute handgrip strength in lean and obese women. This is in accordance with the study of Shepard et al which was performed in older subjects.…”
Section: Discussionmentioning
confidence: 99%
“…Whole body measurements were taken with the patient positioned and the electrodes connected in the standardized position, as described by Baumgartner. 24 The participants had an overnight fast (no eating or drinking) and had taken no medication that could affect water content of the body.…”
Section: Methodsmentioning
confidence: 99%
“…Moreover, adipose tissue could affect measured resistance. When the volume of adipose tissue is greater than muscle volume, a slight overestimation of FFM will result when a BIA equation derived for non-obese female subjects is applied (Baumgartner et al, 1998). An assessment of the accuracy of the TBW and FFM general equation derived from the validation group for each BMI category indicated that the general equation was valid for children across a wide BMI range.…”
Section: Development Of Bia Equationsmentioning
confidence: 99%